Prevalence of Elderly Abuse in Community of Kathmandu - Adhikari, Shova; Shrestha, Pratistha (Janaki Medical College Journal of Medical Science, 2022)
Background and Objectives: Elder abuse is a single or repeated act, or lack of appropriate action, occurring within any relationship where there is an expectation of trust, which causes harm or distress to an older person. Around 1 in 6 elders experience some form of abuse worldwide causing bad impact on health as well as quality life of elders. Most of the studies indicate that elder people are suffered from different types of abuse which include: neglect (isolation, abandonment and social exclusion), violation (of human, legal and medical rights), and deprivation (of choices, decisions, status, finances and respect). Thus, this research was carried out to identify the prevalence of elderly abuse and its associated factors among elderly people. Materials and Methods: A descriptive cross sectional research design was adopted in total 60 samples who were selected by non probability purposive sampling technique. Data was collected through door to door survey using face to face interview schedule using Geriatric Mistreatment Scale (GMS). The collected data was analyzed using descriptive statistics such as frequency, percentage, mean, standard deviation and inferential statistics such as Chi-square test by using Statistical Package of Social Science (SPSS) 16th version. Results: The present study findings revealed that prevalence of elderly abuse was 35%. Among different types of elderly abuse, most of the respondents had faced psychological abuse (38.3%), neglect was faced by 20% of the respondents and 20% had to face financial abuse. Minority (5%) had faced physical abuse and none of the respondents had faced sexual abuse. Overall, 35% of the respondents had faced any form of the elderly abuse. The prevalence of elderly abuse had statistically significant association with living arrangement of elderly people and future saving as p-value was 0.045 and 0.023 respectively. Conclusion: The study was concluded that elderly abuse is prevalent in community of Kathmandu. Therefore, the elders are at risk of getting victim of elderly abuse, so effective screening and awareness regarding prevention of elderly abuse is very essential.